Analysing the tourism activity of seniors by applying the method of participant observation - Głąbiński, Zbigniew (Bulletin of Geography. Socio-economic Series, 2016)
Issues concerning seniors' participation in tourism have been of increasing interest to many researchers. This results from their dynamic growth in the world's most developed societies which, together with cultural changes, contributes to greater participation in various forms of tourism. So far, this phenomenon has been examined by applying quantitative methods, surveys being the most common. Some researchers state that qualitative methods may also be of great use in the analysis of tourist behaviour. Therefore, this article aims at presenting the methodological conditions of participant observation as a qualitative method for analysing such behaviour. Its use is exemplified by research findings on Polish seniors conducted among participants of package tours to various European countries. It presents observations concerning their behaviour in both time and space. Special attention was paid to seniors' motives and the forms of tourism those motives led to.